Given data:
The given expression for the function is f(x)= 5/(x+3).
The expression for one-to-one function is,
![\begin{gathered} (5)/(x_1+3)=(5)/(x_2+3) \\ x_2+3=x_1+3 \\ x_2=x_1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iot6xtvmqjrhsvxrnd6nh2k3f0xszxz4b0.png)
The above expression shows that the given function is one-to-one.
The expressionn for the inverse function is,
![\begin{gathered} y=(5)/(x+3) \\ y(x+3)=5 \\ xy+3y=5 \\ xy=(5-3y) \\ x=(5-3y)/(y) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/28rhxmx0zzt6o6i3g7k470xcqmfkqagr21.png)
Replace y by x in the above expression.
![f^(-1)(x)=(5-3x)/(x)](https://img.qammunity.org/2023/formulas/mathematics/college/d7sng38y5f4rteyde60h5h6cp5i6t1ju1m.png)
Thus, the given function is one-to-one and the expression for the inverse function is (5-3x)/x .